WebAssembly: Yes, but for What? - Wingo, Andy (Communications of the ACM, 2025)
WebAssembly (Wasm) has proven effective for porting large C and C++ desktop applications to the Web and embedding components such as file handlers, per-pixel processors, and libraries like SQLite. Its strengths lie in use cases that require strong isolation between program components, such as browser plug-ins, virtualization, or security-critical software, while traditional web languages like JavaScript and TypeScript remain better suited for user-facing interfaces. Wasm also shows promise in cloud and confidential computing due to its fast cold-start characteristics, minimal abstraction overhead, and robust memory-safety guarantees, suggesting potential applications in operating-system drivers, isolated modules, or artificial intelligence tasks that handle sensitive data. Overall, the platform’s pattern of success points to environments where isolation, security, and controlled execution are prioritized.